Analisis Kualitas Air Di Lahan Reklamasi Pertambangan Nikel Desa Mohoni, Petasia Timur, Morowali Utara - FX Anjar Tri Laksono; Indra Permanajati; Rahmat Mualim (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2020)
In Mohoni Village, East Petasia District, North Morowali Regency there are nickel mining activities that are carried out by PT. Asiamax Mining Indonesia. Several locations were mine out status. Hence, reclamation programs are made to improve environmental conditions before mining. One of these stages is water quality tests to ensure that the reclamation area is worthy to be a habitat for animals and plants. The purpose of this study is to find out the water quality in the reclamation area of the ex-nickel mining in Mohoni Village. The storet method is used to analyze water quality whose test parameters include pH, total suspanded solid (TSS), concentrations of copper (Cu), cadmium (Cd), zinc (Zn), lead (Pb), nickel (Ni), chromium valence 6, iron (Fe), manganese (Mn), and cobalt (Co) once every three months for a year.The quality water check results are compared with the environmental quality standards in accordance with law number 32 of 2009. Based on the average monitoring results show that the water quality is classified as moderately polluted. The conclusion from this study is that reclamation land might be not used as habitat for animals and plants because the availability of water is not suitable for consumption